Cura y locura de Juan Tovar: Entre Aristóteles, Artaud y Luisa Josefina Hernández - Palacios, Felipe Reyes (Latin American Theatre Review, 2007)
This homage to Artaud, which at first glance appears as a concentrated biography of his most important moments (as magnetic actor, the travels to Mexico and Ireland, the psychological treatment of Rodez and his final troubled years in Paris), is presented as an exercise in acting. It confronts the discursive principles of the Aristotelian theatre that prevailed up to the 20th century with the possibility of another principle that proposes to recover the sacred, orginary dimensions of the theatre. Even though establishing the ritual sacrifice as the nucleus of the Artaudian conception is debatable, this convincing biographical and theatrical re-creation by the Mexican playwright Juan Tovar in Cura y locura legitimizes the sacrifice of Artaud himself in what Luisa Josefina Hernández, Tovar’s professor of theatre, would call a “tragic farce.” (FRP, Article in Spanish)